PROCESSOS E EXPERIÊNCIAS DA ARTISTA E PROFESSORA DILMA GOES NO ENSINO SUPERIOR - Mattos, Ivana de Macedo (2021)
This paper thesis chooses, as study object, the analysis of Artist and Professor Dilma Góes’ processes and experiences, as well as her and performance in Espírito Santo University Arts Center in order to go through her career in art and teaching from her start as a Professor (1968) until retirement (1992). It states as investigative question: How does the artist's experience contribute to teaching? How are knowledge and art experience fields interconected to teaching experience and knowledge? In order to understand this articulation in the areas of Education and Art of Dilma Góes in her teaching and in her artistic production, we went back to the past until covering testimonials and conversations in the present including, in this research, the field of the history of Art Education in the state of Espírito Santo, specifically, in a course that covered the Institute of Fine Arts (1910-1913), followed by the period of the School of Fine Arts in its two physical spaces (1951-1971), until the year 1972, when it effectively settled in the Campus of Goiabeiras, former UFES Arts Center. We analyzed an important document, a report dated 1973, which contextualized spatially and temporally the year 1972, as well as the organizational and administrative structure to which the teachers were submitted, and the projects of restructuring the subjects for the Undergraduate courses in Design and Plastic and the Bachelor's degree in Plastic Arts. The conceptual and methodological framework of discursive semiotics and plastic semiotics was based on Greimas and Fontanille (1993), Landowski (2002, 2003, 2014), Rebouças (2003) and Oliveira (2004, 2002, 2013), to analyze the narrative paths in the teaching and documents artist, articulating them to the narrative paths obtained in interviews/conversations. The life story methodology related here, through the narratives of Dilma Góes, allowed us to follow the dynamism of its identity process, woven by the processes and experiences constituted in formations, teaching, art and life, permeated by continuities, ruptures and discontinuities. After analyzing Professor Dilma Góes artistic and teaching practices and experiences, it is understood that there is no way to separate them, because we understand that Dilma's life is presented/intertwined in her work/textile production, in the course of her life as an artist and teacher. This investigation covers an UFES Arts Center period in order to give visibility to the memory and history of teaching in Art in Education in order to praise Undergraduate Art teaching background.